From waste rubber to customized graphene/polymer nanocomposites: Thermal stability, flame retardancy and electrical conductivity - Paulina Wiśniewska; Natalia A. Wójcik; Józef Haponiuk; Jacek Ryl; Henri Vahabi; Krzysztof Formela; Mohammad Reza Saeb (eXPRESS Polymer Letters)
Waste rubber management through developing blends of thermoplastics with ground tire rubber (GTR) has gained significant attention for creating sustainable, high-performance materials with enhanced properties. In this work, we developed customized graphene/polymer nanocomposites applying GTR, ethylene-vinyl acetate copolymer (EVA), and graphene nanoplatelets (GNPs), taking carbon black (CB) as the reference additive. A wide range of electrical conductivity from 10–12 S/cm (dielectric) to 10–5 S/cm (semiconductor) was obtained for optimized composites containing GNPs and CB, respectively. Thermal, mechanical, and flame-retardant properties looked promising for additive manufacturing, while electrical conductivity was tailored for soft electronics. In view of processability, mechanical strength, and elasticity, GNPs-incorporated EVA/GTR composites showed an edge over their CB-aided counterparts. For example, tensile strength and elongation at break of EVA/GTR blends reinforced with 20 phr GNPs were 4.8 MPa and 681%, respectively, compared to 4.0 MPa and 651% for the composite comprising an identical amount of CB. Interestingly, combining GNPs and CB enhanced the thermal stability and flame retardancy of EVA/GTR compared to only GNPs or CB. These results were promising from both sustainability and advanced functional materials perspectives.